The heretic's guide to global finance : hacking the future of money - Scott, Brett (Pluto Press, 2013)
This book is a practical guide for anyone who wants to deepen their understanding of the inner workings of finance, and gain access to it. It explores how financial knowledge can be used to build effective social and environmental campaigns, and shows how activists can tap into the internal dynamics of the sector to disrupt it. -- Back cover.